Fatal women of Romanticism - Craciun, Adriana, 1967- (Cambridge studies in Romanticism, 2003)
Adriana Craciun demonstrates how portrayals of femmes fatales or fatal women played an important role in the development of Romantic women's poetic identities and informed their exploration of issues surrounding the body, sexuality and politics. Craciun covers a wide range of writers and genres from the 1790s through the 1830s.